Online collaboration as a pedagogical approach to learning and teaching undergraduate legal education. Issue 1 (2nd January 2018) - Bugden, Lisa; Redmond, P.; Greaney, J.
ABSTRACT: Legal education is in a period of rapid development driven by changing industry demands and developing technologies. This paper will describe an innovative pilot study which utilises new technologies to provide an alternative mode of teaching and learning to meet growing industry demands for graduates who are technologically savvy and have strong communication and collaboration skills. The pilot study redesigns a law unit combining a more traditional approach with an approach in which online collaboration is critical to student learning as a teaching and assessment tool. After completing an online collaborative activity as part of their assessment for the unit, students completed an online survey to identify their perspectives of the online collaborative experience. The online survey data was analysed to identify common themes and the experiences of students are shared in this paper. The paper provides an example of how instructors might take advantage of a learning design process, online tools and infrastructure to develop educational experiences which promote communication and collaboration within the law discipline. It will also include five recommendations to consider when including online collaboration in unit design for law students.